Formation of Professionally Significant Personal Qualities of Future Specialists in the Sphere of Services and Tourism by Means of Self-Management - Zinkova, Iryna (Pedagogical Discourse, 2019)
In the article the scientific substantiation of peculiarities of formation of professionally significant qualities of the future specialists in the sphere of services and tourism has been covered. On the basis of theoretical and methodological studies the results of scientific researchers, the understanding of the key categories, such as «professionally important qualities» and so on have been analyzed. Such qualities include communicativeness, innovation, creativity, client orientation, initiative, risk-taking, organizational skills. The formation of professionally significant qualities has been accomplished in the educational process during the forming experiment on the problem of forming the entrepreneurial culture of students studying in the specialties 242 – «Tourism» and 241 – «Hotel and Restaurant Business». The tasks have been solved by introducing a special course «Entrepreneurial Culture of Specialist Services and Tourism: Theory and Practice», using self-management tools and supplementing the content of the program of different types of practices. The article highlights the peculiarities of familiarizing students with the conditions and factors of improving self-management in accordance with the established functions of self-management, such as: correct definition of personal goals, planning activities, technology organization activities, self-control and formulation of conclusions, effective use of time, ability to manage stress, etc. Forms, methods and techniques of students’ self-management skills during higher education have been presented, namely: group work, brainstorming, project technology, introspection. In this way, students were introduced to the theoretical basics and learned practical self-management skills.